Application of a New Spirometric Reference Equation and Its Impact on the Staging of Korean Chronic Obstructive Pulmonary Disease Patients - Hwang, Yong Il (Yonsei University College of Medicine, 2012)
PURPOSE: A new spirometric reference equation was recently developed from the first national chronic obstructive pulmonary disease (COPD) survey in Korea. However, Morris' equation has been preferred for evaluating spirometric values instead. The objective of this study was to evaluate changes in severity staging in Korean COPD patients by adopting the newly developed Korean equation. MATERIALS AND METHODS: We evaluated the spirometric data of 441 COPD patients. The presence of airflow limitation was defined as an observed post-bronchodilator forced expiratory volume in one second/forced vital capacity (FEV1/FVC) less than 0.7, and the severity of airflow limitation was assessed according to GOLD stages. Spirometric values were reassessed using the new Korean equation, Morris' equation and other reference equations. RESULTS: The severity of airflow limitation was differently graded in 143 (32.4%) patients after application of the new Korean equation when compared with Morris' equation. All 143 patients were reallocated into more severe stages (49 at mild stage, 65 at moderate stage, and 29 at severe stage were changed to moderate, severe and very severe stages, respectively). Stages according to other reference equations were changed in 18.6-49.4% of the patients. CONCLUSION: These results indicate that equations from different ethnic groups do not sufficiently reflect the airflow limitation of Korean COPD patients. The Korean reference equation should be used for Korean COPD patients in order to administer proper treatment.